Cyclosporine A in addition to standard ART during primary HIV-1 infection: pilot randomized clinical trial. (13th December 2016) - Nicolás, David; Ambrosioni, Juan; Sued, Omar; Brunet, Mercé; López-Diéguez, María; Manzardo, Christian; Agüero, Fernando; Tuset, Montserrat; Plana, Montserrat; Guardo, Alberto C.; Mosquera, María Mar; Muñoz-Fernández, M. Ángeles; et al.
Abstract : Background: Initiating ART during acute/recent HIV-1 infection reduces viral reservoir formation. It has been proposed that, during this phase, the size of the viral reservoir could be further reduced by the association of immunomodulatory therapy with ART. Contradictory results have emerged, however, from two trials evaluating the impact on immune recovery and the viral reservoir of adding cyclosporine A to ART during primary HIV-1 infection. Patients and methods: Twenty patients with acute/recent HIV-1 infection were randomized to receive ART alone (tenofovir, emtricitabine and lopinavir/ritonavir) or associated with 8 weeks of cyclosporine A (0.3–0.6 mg/kg twice daily). The impact on viral load, immune response and integrated and non-integrated DNA viral reservoir at 0, 8 and 36 weeks of treatment was evaluated. Results: The estimated median time from HIV-1 infection to ART onset was 63 days (IQR 53; 79.5) with 90% of patients at Fiebig V stage. No significant differences were observed in viral load decay, CD4 T cell recovery, immune response markers or the evolution of integrated DNA at week 8 (end of cyclosporine A) and week 36 between groups. However, non-integrated DNA significantly increased in the cyclosporine A arm between weeks 0 and 36. Cyclosporine A was well tolerated. Conclusions: Adding cyclosporine A to ART during acute/recent infection did not improve immune recovery. However, unintegrated DNA increased in the cyclosporine A group, suggesting an anti-integration effect, a point warranting further research (ClinicalTrials.gov Identifier: NCT00979706).